Pengaruh Penerapan Model Pembelajaran Problem Based Learning terhadap Peningkatan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pengantar Ekonomi dan Bisnis - Siti Mitasari; Ria Herdhiana; Bella Anantha Sritumini (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
The purpose of this study was to determine the effect of applying the PBL learning model to improving students' critical thinking skills. The research sample used was class X-Accounting 1 and X-Accounting 2. The first meeting was given a pretest in the control and experiment classes, while the second meeting and the last meeting were given posttest. The control class uses the learning model / method commonly used by the subject teachers while the experimental class uses the PBL learning model. The results of the pretest and posttest data were processed using IBM SPSS version 21 and Microsoft Excel. Hypothesis testing is done using non-parametric techniques. The test results show that the class that uses the PBL learning model has advantages, namely an increase in students' critical thinking skills that are significant compared to the class that does not use the learning model. These advantages are seen from indicators of critical thinking which include the ability to analyze, evaluate and create better after using the PBL learning model. Based on the results of the study, it is recommended to use the PBL learning model in teaching and learning activities in order to develop students' critical thinking skills well.